KEYS-METHOD IN PREPARATION OF FUTURE TEACHERS TO INNOVATIVE PROFESSIONAL ACTIVITY - Kozak, Liudmyla V. (Educological discourse, 2015)
In the offered article is exposed essence of method of keys, his purpose and task, place and value of method in professional preparation of future specialists; are certain the features of method of keys, its principles, structure, influence on forming of high-quality descriptions of specialist; is given technology of preparation of keys and features of his application in preparation future teachers to innovative professional activity.